Revitalisasi Voice sebagai Hak Politik Warga Kota di Indonesia: Suatu Kajian Konseptual - Wasisto Raharjo Jati (Jurnal HAM, 2022)
The idea of voice has been long existing within society. When it comes to current urban environment, it seems that voice has been declining due to firm influence of individualism. This makes the inclusive dialogue space between inter citizens group & government and society relationship faded away. Concerning on this issue,  this paper would like to highlight the possibility of voice to be main drive to rebuild political rights for citizens. By using a mixed method that consists of in-depth interviews and critical literature review, this paper shows that voice recently has been institutionalised into two ways: formal through e-government and informal through community radio broadcasting. Both ways are able to deliver grass root  aspiration to be policymaking issues. These finding of this research suggests the need of active citizen participation to voice their aspiration through different platforms rather than formal ways.